Teaching writing genres across the curriculum : strategies for middle school teachers - Pasquarelli, Susan Lee (Contemporary language education (Greenwich, Conn.), 2006)
This volume showcases the efforts of real teachers using the teaching events from real middle school classrooms. Included is the work of eight hard-working middle school teachers who are convinced that the form and function of genre is a way to teach writing across the middle school curriculum. Each chapter contains sample lessons, protocols, classroom instructional materials, and assessment tools to provide middle school teachers with an approach to explore rigorous expository writing instruction in their own classrooms.